Mini review: Interleukin-32 as a key mediator of type 1 diabetes pathogenesis - Pearson, James A.; Hanna, Stephanie J. (Frontiers in Immunology, 2025)
Type 1 diabetes (T1D) is an autoimmune disease characterized by the destruction of insulin-producing β-cells in the pancreatic islets. The pathogenesis, involving complex interactions between genetic susceptibility and environmental factors, is mediated by T cells driven by multiple stimuli including cytokines. Interleukin-32 (IL-32), a predominantly proinflammatory cytokine, has emerged as a potential contributor to T1D pathogenesis. In this review we discuss current knowledge of IL-32 and its role in T1D pathogenesis, examining expression patterns in PBMCs and islets, possible functional mechanisms, and the potential for IL-32 as a biomarker. We will also consider how immunotherapies currently in clinical trials aiming to slow T1D progression may impact IL-32.